Manajemen Hubungan Masyarakat dalam Membangun Citra dan Partisipasi Masyarakat: Studi pada Pondok Pesantren Darussa’adah Al-Islamy - Khoirinnisa; Khildah Salsabilatun Najah; Maulana Malik Ibrohim; Retno Wijayanti (Al-Kindi, 2026)
This study aims to describe public relations management at Darussa’adah Al-Islamy Islamic Boarding School in building institutional image, strengthening communication with the public, and increasing community participation. This study employed a descriptive qualitative approach through observation, interviews, and documentation of public relations activities in the pesantren. The findings show that public relations management is implemented through four main functions: program planning, organizing human resources, implementing internal and external communication, and evaluating activities. Public relations programs are reflected in public religious gatherings, student admission socialization, publication through social media, communication with parents, alumni involvement, socio-religious activities, and event documentation. Public relations in pesantren does not merely function as an information channel but also as a bridge between the institution, students, parents, alumni, society, and external partners. The obstacles include the absence of a fully structured public relations team, limited digital publication resources, unsystematic documentation, and irregular written evaluation. This study recommends establishing a more organized public relations team, preparing a publication calendar, strengthening digital media, managing parent and alumni databases, and conducting regular evaluations through meetings and written reports. Systematic public relations management can strengthen public trust and improve the quality of Islamic education services.